2021
DOI: 10.1093/milmed/usaa374
|View full text |Cite
|
Sign up to set email alerts
|

Bruxism and Stress Among Veterans With Gulf War Illness

Abstract: Introduction This study explores perceived stress and experience with bruxism among veterans with Gulf War Illness (GWI). Stress may manifest physically as bruxism, a parafunctional oral activity that consists of teeth grinding and/or clenching. Materials and Methods An online survey of GWI veterans (n = 28, 27.7% response rate) assessed perceived general stress and self-reported behaviors, symptoms, and outcomes associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Colonna et al found that almost 50% of 506 participants with poor mental health due to the COVID-19 pandemic reported an increase in bruxism behaviors, and approximately 30% of the participants reported an increase in their TMD symptoms [23]. Carter also reported an association between stress and bruxism among veterans with Gulf War illness [24]; the participants, who had higher levels of perceived stress than the general population, demonstrated a high frequency of teeth grinding and clenching. Bruxism puts pressure on the orofacial muscle, and persistent pressure on this muscle leads to pain in the masseter and temporal muscles.…”
Section: Discussionmentioning
confidence: 99%
“…Colonna et al found that almost 50% of 506 participants with poor mental health due to the COVID-19 pandemic reported an increase in bruxism behaviors, and approximately 30% of the participants reported an increase in their TMD symptoms [23]. Carter also reported an association between stress and bruxism among veterans with Gulf War illness [24]; the participants, who had higher levels of perceived stress than the general population, demonstrated a high frequency of teeth grinding and clenching. Bruxism puts pressure on the orofacial muscle, and persistent pressure on this muscle leads to pain in the masseter and temporal muscles.…”
Section: Discussionmentioning
confidence: 99%
“…Military life can have adverse effects on oral health, leading to toothache, periodontal diseases, and tooth fractures 9 . These dental problems can cause pain and make everyday activities, such as eating, communicating, sleeping and performing military duties challenging 10,11 . Additionally, bad habits such as bruxism, clenching, or tightly closing the mouth may develop 12 .…”
Section: Introductionmentioning
confidence: 99%
“…9 These dental problems can cause pain and make everyday activities, such as eating, communicating, sleeping and performing military duties challenging. 10,11 Additionally, bad habits such as bruxism, clenching, or tightly closing the mouth may develop. 12 The relationship between stress and temporomandibular joint disorders (TMD) is an important topic in health and dentistry, and has been consistently explored in various studies.…”
mentioning
confidence: 99%